2016
DOI: 10.1111/jen.12361
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Dendroctonus simplex to Hypocreales fungi: towards the development of a biological control strategy

Abstract: The use of Hypocreales fungi against bark beetles is an attractive alternative strategy for biological control in forestry. However, fungal inoculation methods remain a major challenge due to the cryptic behaviour of these beetles. Experiments were conducted to evaluate the susceptibility of adult eastern larch beetles, Dendroctonus simplex, to different isolates of Hypocreales fungi and to assess the efficiency of direct inoculation of fungal conidia using an assisted autodissemination device. Among the nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Our results corroborate with that reported by Quesada‐Moraga, Martin‐Carballo, Garrido‐Jurado, and Santiago‐Alvarez, (2008), showing that transmission of entomopathogenic fungus M. anisopliae strain EAMa 01/58‐Su within the populations of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), was higher when males were carriers of the pathogen. However, our findings are contrary to that reported by Srei, Lavallée, and Guertin, (2017), who demonstrated that in Dendroctonus simplex LeConte (Coleoptera: Curculionidae), horizontal transmission of B. bassiana isolate INRS‐242 was higher when females were inoculated with the fungus. Our results therefore revealed the potential of T. absoluta population to horizontally transmit the three M. anisopliae isolates, ICIPE 18, ICIPE 20 and ICIPE 665 inocula and induce high mortality rates under laboratory conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results corroborate with that reported by Quesada‐Moraga, Martin‐Carballo, Garrido‐Jurado, and Santiago‐Alvarez, (2008), showing that transmission of entomopathogenic fungus M. anisopliae strain EAMa 01/58‐Su within the populations of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), was higher when males were carriers of the pathogen. However, our findings are contrary to that reported by Srei, Lavallée, and Guertin, (2017), who demonstrated that in Dendroctonus simplex LeConte (Coleoptera: Curculionidae), horizontal transmission of B. bassiana isolate INRS‐242 was higher when females were inoculated with the fungus. Our results therefore revealed the potential of T. absoluta population to horizontally transmit the three M. anisopliae isolates, ICIPE 18, ICIPE 20 and ICIPE 665 inocula and induce high mortality rates under laboratory conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…For the second treatment, only the EAB male was inoculated with the fungus (IM+UF), whereas in the third treatment, just the EAB female was contaminated with the fungus (IF+UM). Fungal inoculation process using the autodissemination device was performed in this experiment [8]. Briefly, each EAB male or female was left walking on the fungal-coated pouch for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The semiochemical baited traps connected to an auto-inoculative device attract insect pests and then contaminate them with the entomopathogen before returning to the environment to infect other pests horizontally or vertically (Dimbi et al, 2003;Ekesi et al, 2007). Such a dissemination approach can protect entomopathogens from UV exposure and rainfall (Srei et al, 2017). For instance, B. bassiana is introduced into a spruce bark beetle, I. typographus population, via an auto-inoculative device (Kreutz et al, 2004).…”
Section: Entomopathogenic Control Of Coleopteran Beetlesmentioning
confidence: 99%